The conceptual and the linguistic factors in the use of metaphors - Moura, Heronides Maurílio de Melo (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
The purely cognitive representation of metaphor poses some difficulties. It is proposed that these difficulties can be tackled down in the alternative view proposed in this article, according to which there is an interdependence of conceptual and linguistic factors in the use of metaphor. Some linguistic regularities are identified in the interpretations of some types of metaphor, such as personification, and is argued that a richer description of these tyoes if metaphor is obtained if the linguistic knowledge and semantic compositionality of topic and vehicle are taken into asccount.